An Analysis of Chinese Universities Students’ Attitudes towards Native and Non-Native English-Speaking Teachers (NESTs/NNESTs) - Mairi, Salam; Febriani, Sri; Solusia, Carbiriena (J-SHMIC : Journal of English for Academic, 2018)
This study aims to do further investigation on Chinese universities students’ attitudes towards native and non-native English speaking-teachers. It mainly studies two major researches on the topic with at least 368 participants from China (mainly) and Hungary. The study critically reviews the two studies and finds out that the fact about NESTs is unsatisfactory. It requires much improvement because of inexperienced NESTs, lack of responsibility, cultural unfamiliarity, and inability to provide opportunity for students to practice. However, it is inevitable that NESTs are considered better at English proficiency and that they are student-friendly teachers. In another study, students changed their preference over NESTs vs NNESTs because they believe that NESTs help maintaining their motivation to communicate in English. However, they might prefer NNESTs for cultural and linguistic (e.g. grammar explanation) competences. Thus, this study offers recommendations for improvement in the context. The recommendations include course on English proficiency, cultural competence, teaching skill, certification, and communication-focused concept of English materials.